Assembly of upconversion nanophotosensitizer in vivo to achieve scatheless real-time imaging and selective photodynamic therapy. (May 2019) - Feng, Yansong; Wu, Yanni; Zuo, Jing; Tu, Langping; Que, Ivo; Chang, Yulei; Cruz, Luis J.; Chan, Alan; Zhang, Hong
Abstract: A perfect "off" to "on" switch of the therapeutic function is very important to minimize the phototoxicity of nanoplatforms assisted imaging-guided photodynamic therapy (PDT) of cancer. Current approaches rely on preloaded photosensitizers, where the off/on state of PDT is regulated by the sensitizing light of photosensitizers. However, the photoactivities inevitably occur when imaging/diagnosis or exposure to sunlight, etc . These preloading approaches will cause the damage to normal cells and the photosensitivity to the skin. Taking upconversion photodynamic therapy as an example we report here a biorthogonal chemistry solution to circumvent this problem. The luminescence upconversion nanoparticles (UCNPs) are anchored with one handle of click reaction and targeting entity, these nanoplatforms enable the imaging/labelling/tracking, especially for imaging-guided surgery. Once they are targeted, the photosensitizers armed with the other match handle will be injected in situ and click reaction will occur between the two handles to link the photosensitizers closely with the targeted nanoplatforms in a very short time, enabling the PDT function of the nanoplatforms. Proof of principle has been demonstrated in vitro and in vivo . This approach can be readily extended to chemotherapy, radiotherapy, etc. to overcome the side effect of these therapies of cancers. Graphical abstract: Image 1